DYSTOCIA DUE TO PEROSOMUS ELUMBIS WITH SCHISTOSOMUS REFLEXUS IN A BUFFALO - PANDEY, ANAND KUMAR; SINGH, GYAN; BUGALIA, N S; KUMAR, SANDEEP; SYAMSUNDER (The Indian Journal of Animal Reproduction, 2023)
A rare case of combination of two types of monstrosities in a buffalo calf delivered by caesarean operation has been recorded.